Community Clinicians and the Veterans Choice Program for PTSD Care: Understanding Provider Interest During Early Implementation. (July 2017) - Finley, Erin P.; Noël, Polly H.; Mader, Michael; Haro, Elizabeth; Bernardy, Nancy; Rosen, Craig S.; Bollinger, Mary; Garcia, Hector; Sherrieb, Kathleen; Pugh, Mary Jo V.
Abstract : Background: In 2014, the Department of Veterans Affairs (VA) implemented the Veterans Choice Program (VCP) to provide reimbursement for community-based care to eligible veterans. Inadequate networks of participating providers may impact the utility of VCP for veterans with posttraumatic stress disorder (PTSD), a complex condition occurring at lower frequency among civilians. Objectives: To compare characteristics and attitudes of community-based primary care and mental health providers reporting interest or no interest in VCP participation during early implementation; and to examine perceptions and experiences of VCP among "early adopters." Research Design: Cross-sectional surveys with 2 samples: a stratified random sample of mental health and primary care prescribers and psychotherapists drawn from state licensing boards (Community Sample); and a stratified random sample of prescribers and psychotherapists identified as VCP-authorized providers (VCP-Authorized). Subjects: Five hundred fifty-three respondents in the Community Sample and 115 in the VCP-Authorized (total, n=668; 21.1% response). Measures: Surveys assessed provider and practice characteristics, attitudes to VA and VCP, and experiences and satisfaction with the VCP; an open-ended survey item assessed providers' reasons for interest or lack of interest in VCP participation. Results: Few providers reported VCP participation during this period. Interest in VCP participation was associated across provider groups with factors including being a veteran and receiving VA reimbursement; currently providing treatment for PTSD was associated with interest in VCP participation among psychotherapists, but not prescribers. Conclusions: Developing networks of VCP providers to serve Veterans with PTSD is likely to require targeting more receptive provider groups, reducing barriers to participation, and more effectively communicating the value of VCP participation to providers. Abstract : Supplemental Digital Content is available in the text.